Expression of Concern: Bellomo et al. Effect of Bifidobacterium bifidum Supplementation in Newborns Born from Cesarean Section on Atopy, Respiratory Tract Infections, and Dyspeptic Syndromes: A Multicenter, Randomized, and Controlled Clinical Trial. Microorganisms 2024, 12, 1093 - Microorganisms Editorial Office (Microorganisms, 2025)
With this notice, the Microorganisms Editorial Office alerts the readers of concerns related to this article [...]